The effect of loading direction on strain localisation in wire arc additively manufactured Ti–6Al–4V - Lunt, David; Ho, Alistair; Davis, Alec E.; Harte, Allan; Martina, Filomeno; da Fonseca, João Quinta; Prangnell, Philip B. (Elsevier, 2020)
Ti–6Al–4V microstructures produced by high deposition rate Wire Arc Additive Manufacturing (WAAM) can be both heterogeneous and anisotropic. Key features of the as-built microstructures include; large columnar ß grains, an α transformation texture inherited from the β solidification texture, grain boundary (GB) α colonies, and Heat Affected Zone (HAZ) banding. The effect of this heterogeneity on the local strain distribution has been investigated using Digital Image Correlation (DIC) in samples loaded in tension; parallel (WD), perpendicular (ND) and at 45° (45ND) to the deposited layers. Full-field surface strain maps were correlated to the underlying local texture. It is shown that loading perpendicular to the columnar β grains leads to a diffuse heterogeneous deformation distribution, due to the presence of regions containing hard, and soft, α microtextures within different parent β grains. The ‘soft’ regions correlated to multi-variant α colonies that did not contain a hard α variant unfavourably orientated for basal or prismatic slip. Far more severe strain localisation was seen in 45° ND loading at ‘soft’ β grain boundaries, where single variant α GB colonies favourably orientated for slip had developed during transformation. In comparison, when loaded parallel to the columnar ß grains, the strain distribution was relatively homogeneous and the HAZ bands did not show any obvious influence on strain localisation at the deposit layer-scale. However, when using high-resolution DIC, as well as more intense shear bands being resolved at the β grain boundaries during 45° ND loading, microscale strain localisation was observed in HAZ bands below the yield point within the thin white-etching α colony layer.
Keywords: Strain localisation; Digital image correlation; EBSD; Tensile; Additive manufacturing; Titanium alloys